The Effect of Learning Environments Enriched with Multisensory Reading Activities on Reading Comprehension, Reading Comprehension Strategies and Reading Motivation - Yılmazlar, Hande Şeyda; Görgen, İzzet (Universitas Pendidikan Indonesia, 2023)
The aim of the study is to determine the effect of learning environments enriched with multi-sensory reading activities on reading comprehension skills. Within the framework of this general objective, it was also aimed to investigate the effect of learning environments enriched with multi-sensory reading activities on reading comprehension strategies and reading motivation. For these purposes, a quasi-experimental model with a pre-and post-test control group was used in the research model. In the 2020-2021 academic year, the existing Turkish curriculum was used in the control group while the Turkish courses of a private primary school were conducted with the Turkish curriculum enriched with multi-sensory activities prepared by the researcher in the experimental group. The research lasted for 6 weeks. Considering the results obtained from the research, the following results were reached. “The Turkish curriculum enriched with multi-sensory reading activities is more effective than the existing Turkish curriculum in the development of Reading Comprehension Skills.” “In the development of Reading Comprehension Strategies, the Turkish curriculum enriched with multi-sensory reading activities is more effective than the existing Turkish curriculum.” and “The Turkish curriculum enriched with multi-sensory reading activities is more effective than the existing Turkish curriculum in the development of Reading Motivation.”